2019
DOI: 10.3847/1538-4357/ab45e8
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of the Hot Feedback Mode in Active Galactic Nuclei Feedback in an Elliptical Galaxy

Abstract: Depending on the value of the accretion rate, black hole accretion is divided into cold and hot modes. The two modes have distinctly different physics and correspond to two feedback modes. Most previous feedback works either focus only on one mode, or the accretion physics is not always properly adopted. Here, by performing hydrodynamical numerical simulations of AGN feedback in an elliptical galaxy, we show that including both is important, and gives different results from including just one or the other. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 104 publications
4
14
0
Order By: Relevance
“…Among the crucial open questions about LLAGN feedback is whether the hot wind can deposit its kinetic energy and momentum into a substantial volume of the host galaxy, as required to effectively quench star formation in cosmological simulations (Weinberger et al 2017;Pillepich et al 2018). Numerical simulations predict that the hot wind will interact with the circumnuclear medium, releasing its kinetic energy and momentum and potentially creating strong shocks (Yoon et al 2019). The 0.8-keV plasma found in the HETG spectrum might be evidence for such an interaction, which is likely the manifestation of a circumnuclear hot gas shock-heated by the outward propagating hot wind.…”
Section: Comparison With M81* and Implications For Llagn Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the crucial open questions about LLAGN feedback is whether the hot wind can deposit its kinetic energy and momentum into a substantial volume of the host galaxy, as required to effectively quench star formation in cosmological simulations (Weinberger et al 2017;Pillepich et al 2018). Numerical simulations predict that the hot wind will interact with the circumnuclear medium, releasing its kinetic energy and momentum and potentially creating strong shocks (Yoon et al 2019). The 0.8-keV plasma found in the HETG spectrum might be evidence for such an interaction, which is likely the manifestation of a circumnuclear hot gas shock-heated by the outward propagating hot wind.…”
Section: Comparison With M81* and Implications For Llagn Feedbackmentioning
confidence: 99%
“…In fact, numerical simulations involving both the jet and the hot wind have shown that the momentum flux of the wind is always larger than that of jet (Yang et al 2021). The role of the hot wind in star formation and black hole growth has been investigated in detail by Yoon et al (2019). In the influential cosmological simulations of galaxy formation and evolution, IllustrisTNG (Weinberger et al 2017;Pillepich et al 2018), winds from weakly accreting SMBHs are invoked to quench star formation in intermediate-to high-mass galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand its relative importance, we show in the right panel of Figure 2 the power of different mechanisms as a function of accretion rate. The radiative heating (L BH in the plot) dominates over the kinematic power (Ė w in the plot) in the hot accretion mode (Yuan et al 2018;Gan et al 2019;Yoon et al 2019).…”
Section: Summary and Applicationsmentioning
confidence: 99%
“…Both theory and numerical simulations predict that a strong wind must exist in such hot accretion flows [3][4][5][6] . The wind is of special interest not only because it is an indispensable ingredient of accretion, but perhaps more importantly, it is believed to play a crucial role in the evolution of the host galaxy via the so-called kinetic mode AGN feedback 7,8 . Observational evidence for this wind, however, remains scarce and indirect [9][10][11][12] .…”
mentioning
confidence: 99%
“…The bulk of the wind momentum and kinetic energy should be deposited into the interstellar medium (ISM) due to the wide opening angle of the wind, thus providing an effective feedback to the host galaxy and regulating the growth of the SMBH 7,8 . This is supported by the existence of the 0.9-keV component in the X-ray spectrum, which is likely the result of the outward propagating wind shock-heating the ISM.…”
mentioning
confidence: 99%